The Influence of Social Media on Hedonism Lifestyles Among Students of the Faculty of Communication Sciences - Raihani Firdaus; Qori Nursamsiah; Ujang Dede (Trigin Publisher, 2021)
The lifestyle that students do is often a unique thing to talk about. One of them is about the lifestyle of UNINUS students. From this research, we see that respondents have used social media as a role model in their lifestyle. where 2.90% chose often, 2.90% chose always, 26.50% chose sometimes, 38.60% chose never and 29.40% chose never. Then the level of hedonism in respondents is relatively low if you look at the percentage of questions regarding online shopping where respondents choose the option always 8.80%, choose the option sometimes 47.10%, choose the option never 17.6% and 26.50% choose the option often .